AIDS: Need for Policy in the Workplace - Jain, Hem (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper deals with the workplace implications resulting from the incidence of AIDS for employers, AIDS victims, and coworkers of AIDS virus sufferers in North America. It discusses myths and misconceptions about AIDS as well as the medical facts and the legal aspects of the AIDS controversy. It examines the role of human resource management specialists in handling AIDS concerns, such as testing job applicants, terminating employees with the AIDS virus, developing educational programmes, and writing policy statements. Finally, it makes recommendations on how to effectively deal with the AIDS crisis in workplace settings.